Ceramic Material for Sound Absorption. (March 2015) - Iannace, Gino
The acoustic correction of large places for low frequency components can be obtained by inserting acoustic resonators. This paper reports the realization and the experimental verification of acoustic resonators obtained with ceramic material. The sound absorption is obtained by drilling the specimens of ceramic material with a hole size of 2 mm and 5 mm and a thickness of 3.0 cm, 2.0 cm and 0.6 cm. The sound absorption of perforated plates is based on the principle of Helmholtz resonators, which, however, are effective only on narrow frequency bands; so to make the phenomenon of absorption more effective and to increase the range in absorption frequency perforated panels are made, mounted at a suitable distance from a rigid surface. The measurements of the sound absorption coefficient were performed with an impedance tube (Kundt tube) with an internal diameter of 10 cm and with the validity of the measurement of the absorption coefficient in the range of 100 Hz – 1.0 kHz. The measurements of the absorption coefficient were performed, for each specimen, creating a cavity of air between the sample and the behind rigid surface, with the following thicknesses: 25 cm, 20 cm, 15 cm, 10 cm and 5 cm. As expected, for the same specimen, the peak of the absorption coefficient shifts to higher frequencies on decreasing size of the cavity between the specimen and the rigid wall.